Analysis of Hepatic Artery Infusion (HAI) Chemotherapy Using Randomized Trials of Floxuridine (FUDR) for Colon Cancer Patients with Multiple Liver Metastases - Yuanming Li (Gastroenterology Research and Practice)
Colorectal cancer (CRC) is one of the leading causes of cancer-related death, with most of the people who have the disease developing numerous liver metastases. Sixty percent of colon cancer patients have liver metastases. Only 25% of those with resectable hepatic metastases are alive, and recurrence occurs in nearly half of these cases. Regardless of the fact that left-sided cancer has a higher rate of liver metastases, past study reveals that left- and right-sided liver metastatic colon cancer patients have different survival rates. Hepatic artery infusion (HAI) combined with systemic chemotherapy is a treatment option for patients with unresectable liver-only or liver-dominant colon liver metastases. Although HAI has only been performed in a few locations previously, this study used randomized trials of floxuridine (FUDR) to characterize patient selection and first perioperative results during the deployment of a new HAI program. In this research, we also looked at the technical aspects of placing implantable pumps and catheters for HAI chemotherapy, as well as the efficacy, morbidity, and outcomes of this therapy in colon cancer patients with numerous liver metastases. The parameters like toxicity, overall survival rate, response rate, and progression-free response for the suggested therapy are also analyzed. These findings have important implications for colon cancer adjuvant HAI chemotherapy.